2015
DOI: 10.1007/s13202-015-0185-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of water coning phenomenon in naturally fractured oil reservoirs

Abstract: Water coning is a complex phenomenon observed in conventional and unconventional reservoirs. This phenomenon takes place due to the imbalance between viscous and gravitational forces during simultaneous production of oil and water. In a fractured reservoir, controlling of water coning is challenging due to the complexity originates from large number of uncertain variables associated with such reservoirs system. This paper presents a fully coupled poroelastic multiphase fluidflow numerical model to provide a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Fang et al (2017) addressed a similar problem for a gas reservoir. Their observation differs from that of Reda is that, whereas Reda (2016) claims that oil reservoir aquifer strength has a little effect on produced water cut, Fang et al (2017) found great impact of aquifer size and strength on gas productivity and water cut, possibly because of higher dissolved gas in water.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Fang et al (2017) addressed a similar problem for a gas reservoir. Their observation differs from that of Reda is that, whereas Reda (2016) claims that oil reservoir aquifer strength has a little effect on produced water cut, Fang et al (2017) found great impact of aquifer size and strength on gas productivity and water cut, possibly because of higher dissolved gas in water.…”
Section: Introductionmentioning
confidence: 73%
“…Inamullah et al (2015) have shown through simulation that optimum oil production rate is to be reduced to half of that of maximum production rate if the coning effect is to be minimized. Controlling water coning in fractured reservoirs is more challenging than the homogeneous reservoirs because of the rapid movement of water through the fractures (Reda 2016). To counter the problem, Dabiri et al (2017) suggested the benefits of horizontal wells over vertical wells, showing (through simulation) that critical oil production rate in horizontal wells is greater than that of vertical wells in fractured formations.…”
Section: Introductionmentioning
confidence: 99%
“…In a fractured reservoir, controlling water intrusion is challenging due to the complexity that originates from a large number of uncertain variables associated with the representativity of the natural fractures' attributes and spatial distributions. These water intrusion occurrences have been observed and evaluated for a long time by many studies [4][5][6][7][8][9]. Sheng et al [4] present a parametric study that analyses the effect of matrix and fracture permeability, well penetration, vertical anisotropy, aquifer size and gas rate production on water intrusion.…”
Section: Introductionmentioning
confidence: 99%
“…Water invasion is a complex phenomenon observed in oil and gas reservoirs, which will occur due to pressure gradients close to the production well and the imbalance between the viscous and gravity forces around the completion interval [7,8]. There are three essential forces controlling the mechanism, which includes the capillary, viscous and gravity forces [6].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [20] and Shen et al [21] used reservoir cores to analyze the effects of different aquifers on water invasion. Azim [7] proposed a fully coupled poroelastic multiphase fluidflow numerical model to understand the water coning phenomenon in naturally fractured reservoir under the effects of various rock and fluid properties. So far there has been a lot of research work carried out on the performance of water invasion in gas reservoirs.…”
Section: Introductionmentioning
confidence: 99%